Clinical Significance of Discordance Between Fetal Biparietal Diameter and Femur Length - Özkaya, Enis; Başer, Eralp; Okuyan, Erhan; Çakır, Caner; Korkmaz, Vakkas; Küçüközkan, Tuncay (Gynecology Obstetrics & Reproductive Medicine, 2012)
OBJECTIVE: To investigate if fetal biometric discordance (FBD) between biparietal diameter (BPD) and femur length (FL) has an association with estimated fetal weight (EFW), fetal birth weight (FBW) and gestational age (GA) at delivery. STUDY DESIGN: Records of 1496 women with singleton pregnancies who attended to our institution for pregnancy follow-up between January 1st 2009 and January 1st 2010 were retrospectively analyzed. Fetuses with FBD lasting until delivery were identified. Degree of discordance (DOD) was defined as the variation between BPD and FL in terms of days. DOD at the time of initial diagnosis of FBD (DOD-ID) and before delivery (DOD-BD), initial GA at diagnosis of discordance (GADD), GA at delivery, EFW and fetal birth weight (FBW) were determined for each fetus. Correlation and linear regression analysis was used to determine associations between study parameters. RESULTS: GADD positively correlated with FBW (r:0.497, p<0.001) and gestational age at delivery (r:0.313, p=0.001), and negatively correlated with preterm delivery(PD) (r: -0.404, p<0.001). DOD before delivery positively correlated with difference between EFW prior to delivery and actual FBW (r:0.491, p<0.001). CONCLUSIONS: Fetal biometric discordance, especially when diagnosed early in pregnancy is associated with increase in preterm and low birth weight deliveries. Also, increase in DOD-BD may result in FBW miscalculations.